Quantifying Urban form: A Case Study of Rajshahi City (Journal of Bangladesh Institute of Planners, 2012)
The urban areas comprise complex systems of activities, so the study of its form in terms of a few statistical measures is quite taxing. This paper attempts to employ such measures to define the urban form of Rajshahi city in Bangladesh. It evaluated some of the measures to quantify urban form and selected two indices, namely, Gini coefficient and Moran coefficient to quantify the urban form of the study area. Residential floor area and floor area for employment was computed in a tessellated form for quantifying the urban form of the study area. GeoDa software was employed to calculate Moran for both of the residential and employment floor space. From Moran and Gini value it was found that both of these land uses are highly clustered in a few locations of the study area. The two indices together give intuitive results, which is, residences are generally more dispersed and continuous than that of employment. Although this kind of analysis of urban form is better applied in comparative analysis, the present study provides the take off point for further research of urban form in Bangladesh.DOI: http://dx.doi.org/10.3329/jbip.v2i0.9555  Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 39-48